Results from the ARTEMIS DISK global antifungal surveillance study, 1997 to 2005: An 8.5-year analysis of susceptibilities of candida species and other yeast species to fluconazole and voriconazole determined by CLSI standardized disk diffusion testing - (:unkn) unknown (American Society for Microbiology, 2007)
Fluconazole in vitro susceptibility test results for 205,329 yeasts were collected from 134 study sites in 40 countries from June 1997 through December 2005. Data were collected for 147,776 yeast isolates tested with voriconazole from 2001 through 2005. All investigators tested clinical yeast isolates by the CLSI M44-A disk diffusion method. Test plates were automatically read and results recorded with a BIOMIC image analysis system. Species, drug, zone diameter, susceptibility category, and quality control results were collected quarterly. Duplicate (same patient, same species, and same susceptible-resistant biotype profile during any 7-day period) and uncontrolled test results were not analyzed. Overall, 90.1% of all Candida isolates tested were susceptible (S) to fluconazole; however, 10 of the 22 species identified exhibited decreased susceptibility (<75% S) on the order of that seen with the resistant (R) species C. glabrata and C. krusei. Among 137,487 isolates of Candida spp. tested against voriconazole, 94.8% were S and 3.1% were R. Less than 30% of fluconazole-resistant isolates of C. albicans, C. glabrata, C. tropicalis, and C. rugosa remained S to voriconazole. The non-Candida yeasts (8,821 isolates) were generally less susceptible to fluconazole than Candida spp. but, aside from Rhodotorula spp., remained susceptible to voriconazole. This survey demonstrates the broad spectrum of these azoles against the most common opportunistic yeast pathogens but identifies several less common yeast species with decreased susceptibility to antifungal agents. These organisms may pose a future threat to optimal antifungal therapy and emphasize the importance of prompt and accurate species identification. © 2007, American Society for Microbiology.